DEVELOPMENT AND MODELING OF UNMANNED UNDERWATER REMOTELY OPERATED VEHICLE USING SYSTEM IDENTIFICATION FOR DEPTH CONTROL - Mohd Aras, Mohd Shahrieel; Ab Rashid, Mohd Zamzuri; Azhan , Ab. Rahman (Little Lion Scientific Islamabad Pakistan, 2013)
This paper presents the development and modeling of low cost underwater Remotely Operated Vehicle (ROV) for depth control using system identification technique. The ROV was developed by the Underwater Technology Research Group (UTeRG). For Unmanned Underwater Vehicle (UUV), the most crucial issue is the control system. It is needed for the ROV to perform several underwater applications and tasks. In this project, a prototype of the ROV will be developed first. The ROV will be tested on an open loop system to obtain measured input-output signals. Input and Output signals from the system are recorded and analyzed to infer a model. Then, system identification toolbox in MATLAB will be applied to generate a model of the ROV. The experimental testing of ROV only considered the vertical movement. The modeling obtained will be used to design the a suitable controller for depth control. The purpose of depth control is to ensure the ROV to remain stationary at a desired depth by utilizing the pressure sensor as feedback. The simulation studies have been carried out in order to obtain the controller of the ROV. This method is useful to obtain the model of the ROV to design the best controller for depth control. Conventional controller will be used in order to verify the modeling of ROV and gives acceptable performances of system response.